The effect of board members' education and experience on the financial performance of German state-owned enterprises - Marcus Sidki; Lara Boerger; David Boll (Journal of Management and Governance, 2023)
Within state-owned enterprises (SOEs), supervisory board mandates are often given to politicians, many of whom are selected through political processes in which competence is not necessarily the decisive factor. This paper analyzes the impact of this form of governance, examining the business competence level of supervisory board members and their influence on the financial performance of 58 state-owned utility companies in Germany from 2011 to 2016 by applying OLS regression. For this purpose, the biographical backgrounds of 3350 supervisory board members were compiled to discern their education, management, and industry experience. Contrary to our hypotheses, the empirical analyses show no effects for any of the competence dimensions on companies' profitability. In a more detailed analysis, we find that board members with management experience from outside the energy sector seem detrimental to the company, which may indicate self-overestimation bias. This result is robust across different specifications and opens up an interesting new approach to analyzing the impact of board member competence on firm performance. The insignificance of the other competence areas indicates a rather low impact of supervisory boards on SOEs based on their unique institutional setting and in comparison to private sector corporate governance. Overall, this study contributes to both scholars and practitioners by providing new insights in the field of public corporate governance, focusing on the unique situation of the competence of politically connected boards and their influence on SOEs.
Keywords: G30; H19; L32; 650; Public corporate governance; State-owned enterprises; Supervisory boards; Board competence; Experience; Overconfidence bias